Malaysian biomedical and health sciences publications in the ISI database, 1990 to 2005 : a bibliometric study - Hazmir Zainal (Kuala Lumpur : Faculty of Computer Science and Information Technology, University of Malaya, 2008)
The study adopts the bibliometric method to achieve the following objectives; (a) to analyze Malaysian publication contributions in the field of biomedicine and health sciences in terms of the total spread and main channels of research publications; (b), the active authors involved and the pattern of authorship; (c) publication productivity by Malaysian institutions; (d) the pattern of research collaboration in this field; (e) the subject coverage of researches undertaken, and (f) the citations received by published Malaysian works. The sample comprises 3,697 publications by Malaysian authors indexed in the ISI Science Citation Index database from 1990 to 2005. The most productive period was during the 8MP and the trend line indicated a continuing upward trend. Journal articles (73.3%) were the main type of publication produced. More than half (63.7%) of authors (4,178) were one-time contributors. Fifteen authors were identified as the most productive producing an average of 2.7 papers each per year. The majority of publications were multi-authored (89.3%) works. The institutions of higher learning contributed 87 percent of the total publications. The most active institutions were Universiti Malaya (30.9%), Universiti Sains Malaysia (13.4%), Universiti Kebangsaan Malaysia (12.7%), and Universiti Putra Malaysia (10.7%). A total number of 2,413 (63.5%) joint papers were identified and 47.4 percent were the result of international collaboration. Clinical Medicine is the most actively researched area. The spread of the journals that cover Malaysian publications corroborates with the Bradford's Law of Scattering giving the ratio of 44: 152: 581 (core: moderate: peripheral journals). Most Malaysian articles were published in journals with an impact factor of less than 4. Overall, 2,254 Malaysian papers (60.97%) have been cited at least once over the period of study
Thesis (Degree of Master in Library and Information Science) - University of Malaya, 2008.
Keywords: University of Malaya -- Dissertations; Bibliometrics; Medical sciences -- Research -- Evaluation; Dissertations, Academic -- Malaysia; INDAMET